2016
DOI: 10.1175/mwr-d-15-0005.1
|View full text |Cite
|
Sign up to set email alerts
|

Improving High-Resolution Weather Forecasts Using the Weather Research and Forecasting (WRF) Model with an Updated Kain–Fritsch Scheme

Abstract: 2015: Improving High-Resolution Weather Forecasts using the Weather Research and Forecasting (WRF) Model with an Updated Kain-Fritsch Scheme. Mon. Wea. Rev.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
160
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(165 citation statements)
references
References 77 publications
3
160
0
2
Order By: Relevance
“…1). A horizontal resolution of 2.5 km, 50 vertical levels, and an integration time step of 12 s is used in all WRF runs, which allow for deep moist convective systems with a relevant entity to be explicitly resolved (Weisman et al 1997;Bryan et al 2003;Roberts and Lean 2008;Zheng et al 2016). WRF forecasts span over 42 h, from 0000 UTC 11 October to 1800 UTC 12 October 2007.…”
Section: Meteorological Toolsmentioning
confidence: 99%
“…1). A horizontal resolution of 2.5 km, 50 vertical levels, and an integration time step of 12 s is used in all WRF runs, which allow for deep moist convective systems with a relevant entity to be explicitly resolved (Weisman et al 1997;Bryan et al 2003;Roberts and Lean 2008;Zheng et al 2016). WRF forecasts span over 42 h, from 0000 UTC 11 October to 1800 UTC 12 October 2007.…”
Section: Meteorological Toolsmentioning
confidence: 99%
“…Thus, the sensitivity of different microphysics schemes over the Indian monsoon rainfall needs to be evaluated, particularly for very high-resolution models (<10 km). More recently, Zheng et al [2016] identified that cloud microphysics alone was not sufficient to resolve convective processes at higher resolution in the WRF model. They compared high-resolution model simulations (grid increments of 9 km and 3 km) over the U.S. Ramage [1971].…”
Section: Numerical Models For Precipitation Forecastingmentioning
confidence: 99%
“…In addition, high-resolution numerical simulations of local atmospheric flow in regions that include urban areas have begun to provide credible representations of the three-dimensional local atmospheric circulation on horizontal scales of several kilometers [4][5][6][7]. For this study, the WRF model developed at the National Center of Atmospheric Research (NCAR) is utilized.…”
Section: Introductionmentioning
confidence: 99%